(untitled) (Medico Legal Update, 2021)
Background: The pleural effusion is a common clinical problem which can be exudative or transudative in nature due to variety of causes. Measurement of biochemical markers in the pleural fluid is an important measure to distinguish exudative from transudative effusion. Aim of the Study: Is to determine the value of pleural fluid to serum bilirubin ratio to differentiate between transudative and exudative pleural effusion. Patients and Method: Thirty-five patients enrolled in this study, they admitted to medical ward in Baghdad teaching hospital and submitted to clinical, radiological, ultrasonographic examination proved to have pleural effusion from December 2018 to July 2019. Samples of blood and pleural fluid aspirated in the medical ward, analyzedafter 30-60 minute of aspiration. The sample of some cases were analyzed in private laboratories. Serum protein, total serum bilirubin and other investigation according to the condition of the patient like blood urea, serum creatinine, liver function test, sputum of AFB. Pleural fluid analyzed from protein, total bilirubin, cell count, differential and cytology .Pleural biopsy was done to patients suspected to have malignant or tuberculous effusion and grouped at the end of their hospitalization into exudative and transudative effusion according to specific etiology, clinical examination, radiological finding, and then measure the pleural fluid to serum protein ratio, pleural fluid to serum bilirubin for each patient. We depended on pleural fluid to serum protein ratio to compare with pleural fluid to serum bilirubin ratio for differentiation between exudative and transudative pleural fluid. Results: Twenty two patients with exudative effusion and thirteen patients were having transudate according to pleural fluid to serum protein (Light ’s criteria). P-value= 0.002, Fisher. Exact test= 0.001. Twenty three patients with exudative effusion and twelve patients with transudative effusion according to pleural fluid to serum bilirubin ratio. P value= 0.37, Fisher. Exact test = 0.45. Pf/s ratio can increase the sensitivity and specificity of Light ‘s criteria. Conclusions: Pleural fluid to serum bilirubin ratio can’t replace Light’s criteria in differentiation between exudates and transudate pleural effusion. Pf/s bilirubin ratio is a reliable test can easily perform but not common use in our hospital because of its costy and not familial use in our laboratories.